Money laundering : a new international law enforcement model - Stessens, Guy (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2000)
This book gives an analysis of the legal issues raised by the international fight against money laundering. A comparative research of the criminal and preventive law aspects from an international perspective, it contains the most detailed overview yet published on the rules and practices of international co-operation in this area.